Iodine nutrition status in Africa: potentially high prevalence of iodine deficiency in pregnancy even in countries classified as iodine sufficient - Bitamazire Businge, Charles; Longo-Mbenza, Benjamin; Kengne, Andre Pascal (Public Health Nutrition, 2021)
To assess the burden of iodine deficiency in pregnancy in Africa using estimated pregnancy median urinary iodine concentration (pMUIC). Design: pMUIC for each African country was estimated using a regression equation derived by correlating the school-age children (SAC) median UIC (mUIC) and pMUIC from countries around the globe, and the SAC mUIC data for African countries obtained from the Iodine Global Network (IGN) 2017 and 2019 Score cards. Setting: Iodine deficiency was endemic in many African countries before the introduction of iodine fortification, mainly through universal salt iodisation programmes about 25 years ago. There is a scarcity of data on the level of iodine nutrition in pregnancy in Africa. Women living in settings with pMUIC below 150 μg/l are at risk of iodine deficiency-related pregnancy complications. Participants: Fifty of the fifty-five African countries that had data on iodine nutrition status. Results: A cut-off school age mUIC ≤ 175 μg/l is correlated with insufficient iodine intake in pregnancy (pregnancy mUIC ≤ 150 μg/l). Twenty-two African countries had SAC mUIC < 175 μg/l, which correlated with insufficient iodine intake during pregnancy (pMUIC < 150 μg/l). However, nine of these twenty-two countries had adequate iodine intake based on SAC mUIC. Conclusions: There is likely a high prevalence of insufficient iodine intake in pregnancy, including in some African countries classified as having adequate iodine intake in the general population. A SAC mUIC ≤ 175 μg/l predicts insufficient iodine intake among pregnant women in these settings.
Keywords: Iodine deficiency; Urinary iodine concentration; Pregnancy Africa; Pregnancy